E-BOOK USE OPTIMIZES THIRD TRIMESTER PREGNANT WOMEN'S KNOWLEDGE OF EXCLUSIVE BREASTFEEDING - Atik Setyaningsih; Winarsih Winarsih; Zumrotun Naim (Universitas Karya Husada Semarang, 2025)
The coverage of exclusive breastfeeding at Tulang Bawang Baru Community Health Center in 2024 was 42.12% with a target of 80%, That it is necessary to provide education on the use of E-Books as an educational medium about exclusive breastfeeding. The purpose of this study was to determine the effect of education using e-books on the knowledge of third trimester pregnant women about exclusive breastfeeding. The quantitative research design used a pre-experimental design and a one group pretest-posttest approach. The population in this study was all third trimester pregnant women with a sample of 40 respondents using total sampling. Data collection was carried out using a questionnaire. Univariate and bivariate analysis were carried out using a t-test. The average knowledge of third trimester pregnant women about exclusive breastfeeding before being given education using E-Books was 62.83, and after being given education was 84.33. The paired sample t-test obtained a p-value of 0.000 <α 0.005. The educational use of e-books has significantly impacted the knowledge of exclusive breastfeeding among pregnant women in their third trimester in the Tulang Bawang Baru Community Health Center (Puskesmas). The Puskesmas can utilize e-books as an alternative educational medium in their health promotion programs.